La mujer y el liderazgo empresarial (2012)
The aim of this paper was to describe the current leadership situation from the gender perspective and to analyze the circumstances that deter women from achieving high leadership positions in companies. The core of the discussion turned around women's leadership barriers and how these can be overcome through the recognition of the difference of being a woman. We argued that the main issue related to this unequal participation as CEOs is mainly due to stereotypes concerning women's roles, which in many cases are contrary to the leadership roles accepted in most cultures. We point out that women should find their own leadership capacity, according to their own characteristics rather than to imitate the traditional male leadership role.